2019
DOI: 10.1002/asia.201901638
|View full text |Cite
|
Sign up to set email alerts
|

Regulated Single‐Axis Rotations of a Carbonaceous Guest in a van der Waals Complex with an Entropy Cost

Abstract: In at ight host-guest complex assembled solely by nondirectional van der Waals forces, unique motionso ft he guest, such as solid-state inertial rotations, emerge. The regulation of dynamic motions is an important element to be explored for novel functions of such complexes,w hich may be seemingly difficult to achieve because of the nondirectionality of the assembling forces. Ar egulated, single-axis rotation was made possible by choosing an appropriate shape of the guest in the tubular host. Specifically,a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
(159 reference statements)
0
4
0
Order By: Relevance
“…[18] Four chrysene panels within as ingle [4]CC host were spectroscopically equivalent in the 1 HNMR spectra, thus showing the presence of singleaxis rotations of the guest ( Figure S10). [4,6,9] Thep recise two-wheeled structures of [4]CC'(C 59 N) 2 &- [4]CC were revealed by crystallography.The crystal structure showed that the dumbbell-shaped (C 59 N) 2 guest was encapsulated and two rotated disordered orientations were found along the dumbbell axis.T he cylindrical [4]CC hosts were nearly aligned in parallel, and the cylinders were tilted against the dumbbell-shaped guest ( Figure 3a). Thet ilt angle was measured to be 358 8 ( Figure S13), which was identical to that observed with nonpolar [4]CC'(C 60 ) 2 & [4]CC.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[18] Four chrysene panels within as ingle [4]CC host were spectroscopically equivalent in the 1 HNMR spectra, thus showing the presence of singleaxis rotations of the guest ( Figure S10). [4,6,9] Thep recise two-wheeled structures of [4]CC'(C 59 N) 2 &- [4]CC were revealed by crystallography.The crystal structure showed that the dumbbell-shaped (C 59 N) 2 guest was encapsulated and two rotated disordered orientations were found along the dumbbell axis.T he cylindrical [4]CC hosts were nearly aligned in parallel, and the cylinders were tilted against the dumbbell-shaped guest ( Figure 3a). Thet ilt angle was measured to be 358 8 ( Figure S13), which was identical to that observed with nonpolar [4]CC'(C 60 ) 2 & [4]CC.…”
Section: Resultsmentioning
confidence: 99%
“…Forschungsartikel rotational dynamics of spherical guests in cylindrical hosts. [6] Explorations of the functions of the present nitrogen-doped systems are currently under investigation, including by solidstate dynamics. [34]…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…rotational dynamics of spherical guests in cylindrical hosts. [6] Explorations of the functions of the present nitrogen-doped systems are currently under investigation, including by solidstate dynamics. [34]…”
Section: Methodsmentioning
confidence: 99%